Experimental Techniques in Materials and Mechanics. - Suryanarayana, C. (CRC Press, 2011)
IntroductionMaterials Science and EngineeringStructurePropertiesOutline of the BookX-Ray DiffractionIntroductionCrystal StructureProduction of X-RaysAbsorption of X-RaysThe Bragg EquationDiffraction AnglesIntensities of Diffracted BeamsXRD EquipmentExamination of a Typical XRD PatternCrystal Structure DeterminationIndexing the XRD PatternDifferentiation between SC and BCC LatticesComparison with Electron and Neutron DiffractionExperimental ProcedureOptical MicroscopyIntroductionPrinciple of the Optical MicroscopeComponents of the MicroscopeMicroscopic ObservationInformation Derivable from the.